Neuromyelitis optica spectrum disorder presenting with repeated hypersomnia due to involvement of the hypothalamus and hypothalamus-amygdala linkage. (June 2015) - Kume, Kodai; Deguchi, Kazushi; Ikeda, Kazuyo; Takata, Tadayuki; Kokudo, Yohei; Kamada, Masaki; Touge, Tetsuo; Takahashi, Toshiyuki; Kanbayashi, Takashi; Masaki, Tsutomu
We report the case of a 46-year-old Japanese woman with neuromyelitis optica spectrum disorder presenting with repeated hypersomnia accompanied by decreased CSF orexin level. First episode associated with hypothalamic-pituitary dysfunction showed bilateral hypothalamic lesions that can cause secondary damage to the orexin neurons. The second episode associated with impaired memory showed a left temporal lesion involving the amygdala. The mechanism remains unknown, but the reduced blood flow in the hypothalamus ipsilateral to the amygdala lesion suggested trans-synaptic hypothalamic dysfunction secondary to the impaired amygdala. A temporal lesion involving the amygdala and hypothalamus could be responsible for hypersomnia due to neuromyelitis optica spectrum disorder.